Bevat: CDU in Utrecht met H. Noordergraaf; Excelsior Amsterdam. Opnamen voor radioprogramma van K. Amsberg - Noordergraaf, Herman.
Bevat: CDU in Utrecht met H. Noordergraaf; Excelsior Amsterdam. Opnamen voor radioprogramma van K. Amsberg.